A Study on the Potential of Using Seaweed As Biomonitoring Indicator in Kish Island, Iran - Dadolahi-Sohrab, Ali (2003)
The study was carried out to evaluate the use of seaweed as biomonitoring in Kish Island, Iran. Seaweed, sediment and seawater samples were collected bimonthly from June 1999 to April 2000 at 5 different sites. Seaweed samples were collected, identified and biomass recorded for 4 seasons from April 1999 to March 2000. Diversity and biomass differed within sites and seasons. The highest seaweed biomass were recorded from northwest and west sides of study area. The status of selected heavy metals (Cd, Cu, Ni, Pb, V and Zn) were determined in seawater, sediment and 10 dominant seaweed species. Metals level in seawater ranged from 0.02-0.10,0.09-1.22,0.11-0.18,0.27-2.04 and 0.17-0.27 µg l⁻¹ for Cd, Cu, Ni, Pb and Zn, respectively, the metals concentrations were higher during cold seasons compared to the warm seasons. Metal concentrations in sediments ranged from 0.18-0.39, 2.39-4.55, 2.30-11.92, 2.92-5.92, 1.69-4.76, 4.04-9.51 µg g⁻¹ dry weight for Cd, Cu, Ni, Pb, V and Zn, respectively. Higher variations in metal concentrations were observed at sites Symorgh and Darakht-e-Sabz compared to other sites. Metal levels in seaweeds showed considerable variations ranging from 0.44-1.74, 0.76-3.42,0.37-2.23, 0.96-4.47, 0.53-2.16 and 3.44-10.23 f.1g got dry weight for Cd, Cu, Ni, Pb, V and Zn, respectively. Cadmium was lower in Chlorophyta than the other groups. Chlorophyta accumulated more Zn, V, Pb, Ni and Cu than other groups. In addition, variations in metals contents between species were obvious from the same habitat and in several cases within the same taxonomic groups. Generally, heavy metals level in this study were relatively lower than the other parts of the world and in some cases lower than the other parts of the Persian Gulf. Toxicity test experiments were carried out usmg Cystoseira myrica from Kish Island, Iran and Sargassum ilicifolium species from Port Dickson, Malaysia. All selected concentrations of Cd and V and Cu concentrations at above 0.01 mg l⁻¹ showed toxic effects to both species. The toxic effects ofNi and Zn on the C. myrica and S. ilicifolium were at higher concentrations than the other metals and in addition Cu and V appeared to be more toxic than the other elements. Using both species bioconcentration factors of Pb, Zn and Cu were higher than the other metals. This could be related to their electronegativity values. Elements uptake by different parts of S. ilicifolium during light period decreased in the following order: fronds> receptacles> stipes, whereas during dark period, accumulation of Cd, Cu, V and Ni exhibited similar trend to the above order, but Zn and Pb were higher in receptacles followed by fronds and stipes.